2018
DOI: 10.1093/jhps/hny020
|View full text |Cite
|
Sign up to set email alerts
|

Factors increasing risk of failure following hip arthroscopy: a case control study

Abstract: We aimed to identify factors such as pre-arthroscopy and intra-operative variables that were associated with failure of hip arthroscopy as a joint preserving operation. We performed a retrospective analysis of a database containing 344 consecutive hip arthroscopies performed at our institution. Forty-four hips were identified that underwent a subsequent arthroplasty procedure following their hip arthroscopy (cases). Sixty-six control hips (hip arthroscopy with no subsequent arthroplasty) were randomly selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The AI has also previously been evaluated as a prognostic factor for arthroplasty, with Uchida et al 45 demonstrating elevated AI in their cohort experiencing failure (15° vs 11°), although this did not reach significance ( P = .44). In a more recent matched case-control study by Davies et al, 9 the AI and LCEA as well as cartilage wear were directly evaluated as prognostic markers for future conversion to hip arthroplasty. In a group of 44 participants requiring arthroplasty, the investigators reported an average LCEA of 19° and AI of 10.2°, which were both significantly higher than values in the control population that did not require arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The AI has also previously been evaluated as a prognostic factor for arthroplasty, with Uchida et al 45 demonstrating elevated AI in their cohort experiencing failure (15° vs 11°), although this did not reach significance ( P = .44). In a more recent matched case-control study by Davies et al, 9 the AI and LCEA as well as cartilage wear were directly evaluated as prognostic markers for future conversion to hip arthroplasty. In a group of 44 participants requiring arthroplasty, the investigators reported an average LCEA of 19° and AI of 10.2°, which were both significantly higher than values in the control population that did not require arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Reports on the use of arthroscopic techniques for dysplastic hips range from cautionary to favorable, with predictors of failure including age, severity of dysplasia, and cartilage status at the time of surgery. 9-11,23,27,33,40,45 In contrast, arthroscopic techniques used to address conditions such as FAI labral-chondral abnormalities or synovial abnormalities have a high rate of good to excellent results, durable therapeutic gain, and a high rate of return to sport. 13,24,34…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…17 Furthermore, a high prevalence (>70%) of cartilage injury exists in patients undergoing hip arthroscopy for FAIS, 23,36 with the severity affecting the postoperative outcome. 9,12,30,37 Few studies have investigated the association between hip bony morphology and demographic factors with cartilage injury in FAIS 21,22,31,39 and between cam deformity and end-stage hip osteoarthritis. 1 However, lack of consistency in the definition of bony deformity characterizing FAIS and in the classification of cartilage severity makes interpretation of existing literature difficult.…”
mentioning
confidence: 99%
“…Each submission seems almost better than the last. Again, being unable to pick a favourite as I simply cannot decide, I was especially interested in the paper by Davies et al , who help identify factors increasing the risk of failure after hip arthroscopy [ 10 ]. What an excellent contribution.…”
mentioning
confidence: 99%